The language teacher as a supporter of the linguistic ecosystem among young immigrant learners: Beliefs and practices - Lankiewicz, Hadrian (Glottodidactica, 2023)
The objective of the article is to analyze the attitudes of foreign language teachers towards students’ mother tongues or heritage languages, as migrant students to the city of Gdańsk, Poland, use them as a compensation strategy in formal language learning. On the basis of a survey methodology, the author will try to explore language teacher beliefs regarding the perception of the coexistence and the use of other languages (including Polish) in mainstream FL education and attempt to compile good practices in this regard, reported by the teachers surveyed. Referring to his earlier research (Lankiewicz 2013, 2015, 2019, 2020, 2021), the author hypothesizes that language teachers manifesting higher levels of critical language awareness will be more prone to draw upon students’ linguistic repertoires in the education processes, while others will suppress any form of intercomprehension, code-switching or language meshing.